Sistem Klasifikasi Karakteristik Kepribadian untuk Menentukan Jurusan Perguruan Tinggi Menggunakan Metode MOORA dan Teori MBTI (Studi Kasus : SMA Negeri 7 Lhokseumawe) - Mochamad Ari Saptari; Intan Aquiera; Angga Pratama (STMIK Sinar Nusantara, 2023)
Most high school students who want to pursue their study at a tertiary institution have difficulty making a decision. These students are confused and find it tough to make selections about their college majors. As a result, many new students drop out or switch majors after being accepted to their respective universities. In this study, a web-based decision support system was developed to determine college major choices utilizing MOORA Method and MBTI Theory. The purpose of this research is to ensure that students do not make the wrong decision when deciding on majors in higher institutions. The selection of majors is based on the abilities, interests, and personality of each student. The outcomes of these calculations are the final findings of this system's classification, namely recommendations for higher education majors based on the interests and talents of students in SMA Negeri 7 Lhokseumawe. MOORA calculation successfully produces major recommendations based on the grades inputted by students. Based on the findings of the system psychology test, MBTI theory was able to provide important recommendations based on students' interests.